Pharmacophore Identification Through Molecular Docking of Scopoletin as a PFKFB3 Receptor Inhibitor for Anticancer Drug Development - Ilafi, Nadhifa; Da’i, Muhammad (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Cancer is one of the leading causes of death worldwide. Current therapies often have limited effectiveness and significant side effects. The ability of cancer cells to utilize glycolysis for their growth is one of the challenges in the development of cancer therapies. This study aims to identify the pharmacophore of scopoletin molecules and its derivatives as inhibitors of the PFKFB3 receptor, which plays an important role in cancer cell metabolism through the glycolysis process. The method used is in silico molecular docking. The results showed that of the 12 scopoletin derivative compounds tested, compound C1 (modified by removing double bonds in the carbonyl group and hydroxyl group) showed the best performance with a binding energy value of -7.07 kcal/mol, an inhibition constant of 5.35 μM, and the highest pharmacophore fit value of 48.63. Molecular interaction analysis identified amino acid residues TYR424, LYS168, ALA44, LYS47, and THR48 as important binding sites on the PFKFB3 receptor. All test compounds meet Lipinski's rule and show good ADMET profiles, with Human Intestinal Absorption (HIA) values of more than 89%. The removal of the hydroxyl group at the C-7 position provides better binding values for each class of scopoletin derivative compounds, while the methoxy group plays an important role in the interaction with the target protein.